2016
DOI: 10.1007/s00436-016-4911-y
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and identification of Acanthamoeba species from natural water sources in the northeastern part of Thailand

Abstract: Acanthamoeba are found in the environment, particularly in water, all over the world. The genus is currently classified into 20 different genotypes, T1-T20. In this study, 63 natural water samples from 11 provinces in northeast Thailand were collected and cultured on non-nutrient agar plates. Positive samples by culture were subsequently analyzed by molecular methods. The identification of Acanthamoeba was based on morphological features and molecular techniques using PCR and DNA sequencing. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Delafont et al (2013) reported Acanthamoeba from municipal water sources in France. Furthermore, the isolation of Acanthamoeba was also documented in the Gilan region in Iran's surface water (lagoons, lakes and rivers) and freshwater resources (Mahmoudi et al 2015), in natural water samples from 11 provinces in Northeast Thailand (Thammaratana et al 2016), in recreational hot springs from Malaysia (Mohd Hussain et al 2019) and two major water reservoirs in the Philippines (Milanez et al 2020a), including a nationwide survey of Acanthamoeba species and genotypes in various freshwater systems from the Philippines (Milanez et al 2020b).…”
Section: Discussionmentioning
confidence: 97%
“…Delafont et al (2013) reported Acanthamoeba from municipal water sources in France. Furthermore, the isolation of Acanthamoeba was also documented in the Gilan region in Iran's surface water (lagoons, lakes and rivers) and freshwater resources (Mahmoudi et al 2015), in natural water samples from 11 provinces in Northeast Thailand (Thammaratana et al 2016), in recreational hot springs from Malaysia (Mohd Hussain et al 2019) and two major water reservoirs in the Philippines (Milanez et al 2020a), including a nationwide survey of Acanthamoeba species and genotypes in various freshwater systems from the Philippines (Milanez et al 2020b).…”
Section: Discussionmentioning
confidence: 97%
“…However, incidence of AK in developing countries is often related with outdoor activities and risk exposures to dust, soil or water [1]. In Thailand, Acanthamoeba have been isolated from clinical and environmental samples [5,16–19]. Despite its ubiquity in the nature, less than 10 AK cases have been previously reported from Thailand [20], bringing up to the curiosity that the true AK incidence may be underestimated.…”
Section: Discussionmentioning
confidence: 99%
“…The clustering of the MU_AK into T4 monophyletic clade, could be explained that the 0.73% of genetic distances were remained lower than the 5% cut off value which is known to be characteristic of different genotype [11]. To our knowledge, few molecular studies of Acanthamoeba isolated in Thailand have been documented [18,19,36,37]. Clinically, genotypes T4 and T10 were reported to be responsible for Acanthamoeba keratitis cases, while only T4 was identified from a case of Acanthamoeba meningoencephalitis [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have recorded the wide distribution in soil and water, with differing range of thermal tolerance (Table 1). They have been isolated in untreated natural freshwaters, like lakes, ponds, hot springs and waterfalls [14][15][16][17]; and brackish, seawaters, and ocean sediments [18]. They were also isolated from treated waters like domestic water systems, swimming pools, hydrotherapy pools, remedial spas, tap water and drinking water [14,16,19,20].…”
Section: Epidemiology Of Acanthamoeba In Aseansmentioning
confidence: 99%